2022
DOI: 10.4103/ija.ija_305_22
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the electronic stethoscope (FONODOC) as a cardiac screening tool during the preoperative evaluation of children

Abstract: Background and Aims: An electronic stethoscope with an inbuilt phonocardiogram is a potentially useful tool for paediatric cardiac evaluation in a resource-limited setting. We aimed to compare the acoustic and electronic stethoscopes with respect to the detection of murmurs as compared to the transthoracic echocardiogram (TTE). Methods: This was an observational study. Fifty children aged 0–12 years with congenital heart diseases (CHDs) and 50 without CHD scheduled for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…Katarzyna showed that it can be used as a cardiac screening tool for preoperative evaluation of patients prepared for hip replacement surgery [100]. Similarly, in areas with limited resources, an electronic stethoscope with an integrated phonocardiogram might be a valuable tool for pediatric heart examination [101].…”
Section: Preventive Diagnosis and Monitoringmentioning
confidence: 99%
“…Katarzyna showed that it can be used as a cardiac screening tool for preoperative evaluation of patients prepared for hip replacement surgery [100]. Similarly, in areas with limited resources, an electronic stethoscope with an integrated phonocardiogram might be a valuable tool for pediatric heart examination [101].…”
Section: Preventive Diagnosis and Monitoringmentioning
confidence: 99%